A preparation method of lithium iron phosphate@carbon fiber as a positive electrode material for lithium-ion batteries
By heating the raw materials such as lithium salt, iron salt, phosphate and ammonia triacetic acid in a high-temperature inert atmosphere, lithium ferrous phosphate@carbon fiber composite material was obtained, which solved the problems of low conductivity of LiFePO4 and complex preparation process, and achieved the The material's conductivity improvement and process simplification are suitable for the large-scale production of lithium-ion power batteries.
Patent Information
- Application Number
- CN202310031353.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-01-10
AI Technical Summary
The current lithium-ion battery cathode material lithium ferrous phosphate (LiFePO4) has a low conductivity, which limits its application in the field of power batteries, and the preparation process is complex and difficult to produce on a large scale.
Lithium ferrous phosphate, carbon fiber composite material is prepared by thoroughly mixing, and after high temperature heating in an inert atmosphere and cooling naturally.
Through this method, the obtained LiFePO4@ carbon fiber material has improved conductivity, overcomes electrochemical agglomeration during charging and discharging, and has a simple process, is suitable for large-scale industrial production, and is suitable for lithium-ion power batteries.
Smart Images

Figure CN116314790B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical power source material preparation, and more specifically to a lithium ion battery positive electrode material used as a common lithium ion battery or power energy source, and in particular to a preparation method of lithium iron phosphate@carbon fiber, a lithium ion battery positive electrode material. Background Art
[0002] Lithium iron phosphate (LiFePO 4 ) has become the first choice for positive electrode materials of lithium-ion power batteries due to its abundant resources, low price, green environmental protection, stable cycle performance, and good safety. Its preparation method generally follows two routes: direct synthesis using divalent iron as raw material or indirect preparation using trivalent iron as raw material. Divalent iron (such as ferrous oxalate) is unstable, easily oxidized, and not conducive to storage. Therefore, using trivalent iron as raw material, adding a reducing agent, and preparing LiFePO through redox reaction 4 , has become the main method in industry. The reducing agents currently used are mainly elemental iron, CO (or H 2 ) reducing atmosphere, and polymers (such as polyethylene glycol). The selection of suitable reducing agents is currently a research hotspot. On the other hand, the low conductivity limits the 4 Large-scale application in the field of power batteries. One of the improvement methods is physical carbon addition or chemical carbon addition. Compared with physical carbon addition, chemical carbon addition can obtain a uniformly mixed LiFePO 4 @C. For example, "A LiFePO4 positive electrode material for lithium-ion batteries 4 / C preparation method" (CN1964106), using lithium salt, FePO 4 ·4H 2 O and polyethylene glycol are used as raw materials, mixed evenly and sintered under inert gas protection to produce LiFePO 4 / C. This method produces amorphous carbon with limited improvement in conductivity. 4 @C / MXene composite material preparation method" (CN112490426A), using citric acid and ethylene glycol to perform carbon coating by high temperature treatment, and finally realizing the composite of carbon-coated lithium iron phosphate and MXene by electrostatic self-assembly method, and obtaining LiFePO 4 @C / MXene composites, however, the process is too complicated to be produced on a large scale. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a method for preparing lithium iron phosphate@carbon fiber, a positive electrode material for a lithium ion battery.
[0004] The preparation method of the present invention is: lithium salt, iron salt, phosphoric acid (salt) and nitrilotriacetic acid are fully mixed, placed in an inert atmosphere for high temperature heating reaction for a period of time, and then naturally cooled to obtain lithium iron phosphate @ carbon fiber.
[0005] In the above-mentioned preparation method:
[0006] Preferably, the molar ratio of Li, Fe and P is 1 to 1.05:1:1.
[0007] Preferably, the nitrilotriacetic acid N(CH 2 COOH) 3 As powder.
[0008] Preferably, the lithium salt is LiOH·H 2 O, Li 2 CO 3 , CH 3 COOLi·2H 2 O and Li 3 PO 4 .
[0009] Preferably, the iron salt is FePO 4 ·XH 2 O(X=1~4), Fe(NO 3 ) 3 9H 2 O, Fe 2 O 3 or Fe 3 O 4 .
[0010] Preferably, the phosphoric acid (salt) is diammonium phosphate, diammonium hydrogen phosphate, FePO 4 ·XH 2 O(X=1~4),Li 3 PO 4 , lithium dihydrogen phosphate, or phosphoric acid.
[0011] Preferably, the high temperature heating refers to heating from room temperature at a rate of 5-10°C / min to a temperature range of 350-850°C and then calcining at a constant temperature, and the period of time is 4-24 hours.
[0012] Preferably, the inert atmosphere is nitrogen, argon or a mixed gas thereof.
[0013] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0014] 1. Wide range of raw materials, many choices, simple process, suitable for large-scale industrial production.
[0015] 2. During the mixing process, either dry mixing with a ball mill or wet mixing with a ball mill with an appropriate amount of water, ethanol or acetone can be used.
[0016] 3. From the attachment Figure 1 It can be seen that the carbon fiber in the obtained product is in a network shape, which has many beneficial effects: it can effectively improve the 4 The disadvantage of low conductivity can also overcome the electrochemical agglomeration that occurs during the charging and discharging process, and finally it can be used as a skeleton to maintain the stability of the material.
[0017] 4. The method of the present invention is simple to operate, and the product has excellent electrochemical properties and high rate capacity, and can be widely used in lithium-ion (power) batteries.
[0018] 5. Compared with divalent iron, trivalent iron is cheaper and more convenient to store as an iron source. The reducing agents used in the current technology mainly include iron, polyethylene glycol or sodium polystyrene sulfonate-co-sodium maleate, polyvinyl pyrrolidone, etc., such as the invention patent application CN1964106A - A lithium-ion battery positive electrode material LiFePO 4 / C preparation method, CN103050697A - A method for preparing micron-sized LiFePO4 / C, a high-rate lithium-ion battery positive electrode material. The present invention uses nitrilotriacetic acid as a reducing agent to reduce trivalent iron to divalent iron. This design further enriches the LiFePO 4 Preparation method.
[0019] 6. Compared with carbon particles of other morphologies, the one-dimensional carbon fiber structure provides a short diffusion path for electrons / lithium ions, which more effectively improves LiFePO 4 Disadvantage of poor conductivity.
[0020] 7. In the production process of lithium iron phosphate material prepared by solid phase coordination method of invention patent application CN102437327A, nitrilotriacetic acid is used as a coordination group to react with divalent iron. The coordination effect of nitrilotriacetic acid is different from the reduction effect of this technology, and the inventory of divalent iron in production is not as convenient and practical as the trivalent iron in the present invention. This new mechanism obtains different powders and exhibits different electrochemical properties. Compared with invention patent application CN106898739A - Carbon fiber modified lithium iron phosphate material, positive electrode, lithium battery and preparation method for lithium ion battery positive electrode, bacterial cellulose is used, and LiFePO is prepared by successively undergoing freezing, crushing, soaking, adjusting pH value, filtering, drying and high-temperature calcination. 4 / Carbon fiber. The method is completed in two steps, with simple process and few equipment requirements.
[0021] 8. The synthesized product has many advantages: LiFePO is obtained during the reaction 4@Composite materials with uniform carbon fiber distribution solve the problem of uneven physical addition of conductive agents. The accumulated carbon fibers can also improve the problem of electrochemical agglomeration and alleviate the problem of LiFePO 4 The volume change during charge and discharge results in stable cycle performance, which is very suitable for flexible electronic devices.
[0022] 9. The lithium source, iron source and phosphorus source in the present invention can be processed by dry mixing or wet mixing with the addition of a dispersant, which is highly industrially feasible. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The LiFePO obtained in Example 1 4 @Scan electron microscope image of carbon fiber powder.
[0024] Figure 2 The LiFePO obtained in Example 1 4 @X-ray diffraction pattern of carbon fiber powder.
[0025] Figure 3 The LiFePO obtained in Example 1 4 @X-ray Photoelectron Spectrometer analysis of carbon fiber powder.
[0026] Figure 4 The LiFePO obtained in Example 1 4 @Energy Dispersive X-Ray Spectroscopy of carbon fiber powder.
[0027] Figure 5 The LiFePO obtained in Example 1 4 @ Carbon fiber powder as positive electrode material in batteries at 0.2mV·s -1 The cyclic voltammogram below.
[0028] Figure 6 The LiFePO obtained in Example 1 4 @2000 cycle capacity of a battery using carbon fiber powder as the positive electrode material at 10C; because the picture is in black and white, the "charge" curve and the "discharge" curve are almost overlapping and difficult to distinguish, and are now marked with text in the picture.
[0029] Figure 7 The LiFePO obtained in Example 1 4 @The first and 2000th charge and discharge curves of a battery with carbon fiber powder as the positive electrode material at 10C.
[0030] Figure 8 The LiFePO obtained in Example 1 4 @The battery with carbon fiber powder as the positive electrode material has a voltage drop of 0.2mV·s after 2000 charge and discharge cycles at 10C. -1 The cyclic voltammogram below.
[0031] Fig. 9 The LiFePO obtained in Example 1 4 @Cyclic voltammograms at different scan rates of a battery with carbon fiber powder as the positive electrode material after 2000 charge and discharge cycles at 10C.
[0032] Fig.10 The LiFePO obtained in Example 1 is 4 @The rate capacity of the battery with carbon fiber powder as the positive electrode material.
[0033] Fig.11 The LiFePO obtained in Example 2 4 @The rate capacity of the battery with carbon fiber powder as the positive electrode material.
[0034] Fig.12 The LiFePO obtained in Example 3 4 @The rate capacity of the battery with carbon fiber powder as the positive electrode material.
[0035] Fig.13 The LiFePO obtained in Example 4 4 @The rate capacity of the battery with carbon fiber powder as the positive electrode material.
[0036] Fig.14 The LiFePO obtained in Example 5 4 @The rate capacity of the battery with carbon fiber powder as the positive electrode material.
[0037] Fig.15 The LiFePO obtained in Example 6 4 @The rate capacity of the battery with carbon fiber powder as the positive electrode material.
[0038] Fig.16 The LiFePO obtained in Example 7 4 @Rate capacity of batteries with carbon fiber powder as positive electrode material. DETAILED DESCRIPTION
[0039] In molar ratio Li:Fe:P:N(CH 2 COOH) 3 =1.0~1.05:1:1:0.2~2. Weigh the raw materials and mix them thoroughly. Then, calcine them in an inert atmosphere at a constant temperature of 350~850℃ for 4~24 hours and cool them naturally to obtain lithium iron phosphate@carbon fiber powder.
[0040] The present invention will be further described below in conjunction with the embodiments.
[0041] The chemicals used in the examples are analytically pure powders provided by Sinopharm Chemical Reagent Co., Ltd. The chemical formulas of the relevant raw materials are: Li 2 CO 3 , LiOH·H 2 O, Li 3 PO 4 , CH 3 COOLi·2H 2 O,FePO 4 ·4H 2 O,Fe(NO 3 ) 3 9H 2 O, Fe 2 O 3 , Fe 3 O 4 ,N(CH 2 COOH) 3 , NH 4 H 2 PO 4 , (NH 4 ) 2 HPO 4 .
[0042] Example 1
[0043] Take 0.63g of lithium hydroxide monohydrate (LiOH·H 2 O), 3.34 g ferric phosphate tetrahydrate (FePO 4 ·4H 2 O) and
[0044] 3.18 g nitrilotriacetic acid (N(CH 2 COOH) 3 ), mixed, ball-milled in a ball mill with ethanol as a lubricant for 2 hours, then placed in a tube furnace (Hefei Kejing, GSL 1700X), heated from room temperature to 650°C at a rate of 8°C / min in a nitrogen flow, and then calcined at a constant temperature for 8 hours, and naturally cooled to obtain lithium iron phosphate @ carbon fiber powder.
[0045] The scanning electron microscopy, X-ray powder diffraction and X-ray photoelectron spectroscopy analysis of the obtained products are as follows: Figure 1 , 2 , as shown in Figure 3.
[0046] The product was used as the positive electrode material of lithium-ion battery to prepare the positive electrode of the battery, and metallic lithium was used as the negative electrode to assemble a simulated battery. -1Cyclic voltammetry Figure 5 As shown. At 10C (1C = 170 mAh g -1 ) The charge and discharge test was carried out at a constant current and a voltage of 2.4-4.2V. After 2000 cycles, the charge capacity was 91.2mAh g -1 , discharge capacity is 99.1mAh g -1 (like Figure 6 The charge and discharge curves are shown in Figure 7 After 2000 charge and discharge cycles, the voltage at 0.2mV·s -1 The three cyclic voltammetry curves are highly overlapped (such as Figure 8 The cyclic voltammetry curves at different scan rates (as shown in FIG. Fig. 9 The capacities of the 2C, 5C, 8C and 10C rates are 127.1, 109.7, 99.8 and 98.2 mAh g -1 (like Fig.10 When the rate is reduced to 2C, the capacity is restored to 125 mAh g -1 , indicating that the battery has excellent rate performance, and the prepared lithium iron phosphate@carbon fiber powder is suitable for use as the positive electrode material of lithium power batteries.
[0047] Example 2
[0048] Take 0.66g of lithium hydroxide monohydrate (LiOH·H 2 O), 3.34 g ferric phosphate tetrahydrate (FePO 4 ·4H 2 O) and 5.73 g nitrilotriacetic acid (N(CH 2 COOH) 3 ), mixed, ball milled in a ball mill for 2 hours with ethanol as a lubricant, then placed in a tube furnace (Hefei Kejing, GSL 1700X), heated from room temperature to 850°C at a rate of 10°C / min in a nitrogen flow, and then calcined at a constant temperature for 4 hours, and naturally cooled to obtain lithium iron phosphate @ carbon fiber powder. The remaining process and electrochemical performance test conditions are the same as those in Example 1.
[0049] The capacities at 2C, 5C, 8C and 10C rates are 131.9, 114.2, 103.5 and 95 mAh g, respectively. -1 (like Fig.11 When the rate is reduced to 2C, the capacity is restored to 124.6 mAh g -1 .
[0050] Example 3
[0051] Take 0.63g of lithium hydroxide monohydrate (LiOH·H 2O), 3.34 g ferric phosphate tetrahydrate (FePO 4 ·4H 2 O) and 0.57 g nitrilotriacetic acid (N(CH 2 COOH) 3 ), mixed, ball milled in a ball mill for 2 hours with ethanol as a lubricant, then placed in a tube furnace (Hefei Kejing, GSL 1700X), heated from room temperature to 350°C at a rate of 5°C / min in a nitrogen flow, and then calcined at a constant temperature for 24 hours, and naturally cooled to obtain lithium iron phosphate @ carbon fiber powder. The remaining process and electrochemical performance test conditions are the same as those in Example 1.
[0052] The capacities at 2C, 5C, 8C and 10C rates are 122.4, 104.5, 97.9 and 92.2 mAh g, respectively. -1 (like Fig.12 When the rate is reduced to 2C, the capacity is restored to 116.1 mAh g -1 .
[0053] Example 4
[0054] Take 0.56g lithium carbonate (Li 2 CO 3 ), 6.06 g ferric nitrate nonahydrate (Fe(NO 3 ) 3 9H 2 O), 1.73 g ammonium dihydrogen phosphate (NH 4 H 2 PO 4 ) and 2.87 g nitrilotriacetic acid (N(CH 2 COOH) 3 ), mixed, ball milled in a ball mill for 2 hours with ethanol as a lubricant, then placed in a tube furnace (Hefei Kejing, GSL 1700X), heated from room temperature to 650°C at a rate of 8°C / min in a nitrogen flow, and then calcined at a constant temperature for 8 hours, and naturally cooled to obtain lithium iron phosphate @ carbon fiber powder. The remaining process and electrochemical performance test conditions are the same as those in Example 1.
[0055] The capacities at 2C, 5C, 8C and 10C rates are 126.6, 118.5, 107.1 and 100.5 mAh g, respectively. -1 (like Fig.13 When the rate is reduced to 2C, the capacity is restored to 126.8 mAh g -1 .
[0056] Example 5
[0057] Take 1.53g lithium acetate dihydrate (CH 3 COOLi·2H 2O), 1.2g iron oxide (Fe 2 O 3 ), 1.73 g diammonium phosphate (NH 4 H 2 PO 4 ) and 2.87 g nitrilotriacetic acid (N(CH 2 COOH) 3 ), mixed, ball milled in a ball mill for 2 hours with ethanol as a lubricant, then placed in a tube furnace (Hefei Kejing, GSL 1700X), heated from room temperature to 650°C at a rate of 8°C / min in a nitrogen flow, and then calcined at a constant temperature for 8 hours, and naturally cooled to obtain lithium iron phosphate @ carbon fiber powder. The remaining process and electrochemical performance test conditions are the same as those in Example 1.
[0058] The capacities at 2C, 5C, 8C and 10C rates are 119.7, 104, 91.9 and 83.5 mAh g, respectively. -1 (like Fig.14 When the rate is reduced to 2C, the capacity is restored to 123.4 mAh g -1 .
[0059] Example 6
[0060] Take 0.58g lithium phosphate (Li 3 PO 4 ), 1.16g ferroferric oxide (Fe 3 O 4 ), 1.15 g ammonium dihydrogen phosphate (NH 4 H 2 PO 4 ) and 2.87 g nitrilotriacetic acid (N(CH 2 COOH) 3 ), mixed, ball milled in a ball mill for 2 hours with ethanol as a lubricant, then placed in a tube furnace (Hefei Kejing, GSL 1700X), heated from room temperature to 650°C at a rate of 8°C / min in a nitrogen flow, and then calcined at a constant temperature for 8 hours, and naturally cooled to obtain lithium iron phosphate @ carbon fiber powder. The remaining process and electrochemical performance test conditions are the same as those in Example 1.
[0061] The capacities at 2C, 5C, 8C and 10C rates are 134.7, 117.7, 106.4 and 99.7 mAh g, respectively. -1 (like Fig.15 When the rate is reduced to 2C, the capacity is restored to 123.8 mAh g -1 .
[0062] Example 7
[0063] Take 0.63g of lithium hydroxide monohydrate (LiOH·H 2O), 1.2g iron oxide (Fe 2 O 3 )、1.98 g diammonium hydrogen phosphate ((NH 4 ) 2 HPO 4 ) and 2.87 g nitrilotriacetic acid (N(CH 2 COOH) 3 ), mixed, ball milled in a ball mill for 2 hours with ethanol as a lubricant, then placed in a tube furnace (Hefei Kejing, GSL 1700X), heated from room temperature to 650°C at a rate of 8°C / min in a nitrogen flow, and then calcined at a constant temperature for 8 hours, and naturally cooled to obtain lithium iron phosphate @ carbon fiber powder. The remaining process and electrochemical performance test conditions are the same as those in Example 1.
[0064] The capacities at 2C, 5C, 8C and 10C rates are 128.7, 110.8, 103.2 and 95.9 mAh g, respectively. -1 (like Fig.16 When the rate is reduced to 2C, the capacity is restored to 124.4 mAh g -1 .
Claims
1. A method for preparing lithium iron phosphate@carbon fiber as a positive electrode material for lithium-ion batteries, characterized in that: A lithium source, an iron source, a phosphorus source, and nitrilotriacetic acid are weighed in a molar ratio of Li:Fe:P:N(CH2COOH)3=1.0~1.05:1:1:0.2~2, mixed, and then ball-milled in a ball mill, and then calcined at a constant temperature in a tube furnace under an inert atmosphere, and cooled naturally to obtain lithium iron phosphate@carbon fiber powder, wherein the carbon fiber in the obtained product is in a network shape, and the lithium iron phosphate particles are dispersed in the network-like carbon fiber; The iron source is Fe2O3, Fe3O4, FePO4•XH2O and / or Fe(NO3)3•9H2O, wherein X=1~4; The nitrilotriacetic acid used is powdered and has a reducing effect; The constant temperature roasting refers to heating from room temperature to 350-850° C. at a rate of 5-10° C. / min and then constant temperature roasting, and the roasting time is 4-24 hours.
2. The preparation method according to claim 1, characterized in that: The lithium source is LiOH•H2O, Li2CO3, CH3COOLi•2H2O and / or Li3PO4.
3. The preparation method according to claim 1, characterized in that: The phosphorus source is ammonium dihydrogen phosphate, diammonium hydrogen phosphate, iron phosphate, lithium phosphate, lithium dihydrogen phosphate and / or phosphoric acid.
4. The preparation method according to claim 1, characterized in that: The ball milling in the ball mill refers to dry mixing in a ball mill, or wet mixing in a ball mill with an appropriate amount of water, ethanol or acetone added.
5. The preparation method according to claim 1, characterized in that: The inert atmosphere used is nitrogen or argon or a nitrogen-argon mixed gas.
Citation Information
Patent Citations
Method for preparing micron-sized LiFePO4 / C serving as high-rate lithium ion battery anode material
CN103050697A
Carbon fiber modified positive pole lithium iron phosphate material for lithium ion battery, positive pole, lithium battery and preparation method
CN106898739A
Preparation method of LiFePO4 (at) C / MXene composite material
CN112490426A
A method to manufacture anode material of LiFePO4 / C for lithium ion cell
CN1964106A
Lithium iron phosphate / nano carbon composite material and preparation method thereof
CN101834288A